Rare and interesting plant of Mahonia imbricata T.S. Ying & Boufford – an addition to India from the Manipur State - Dhatchanamoorthy, Narayanasamy; Ravikumar, Kaliamoorthy; Lokho, Kreni; Tangavelou, Arumugame Chanemougame; Begum, Syed Noorunnisa (Biodiversity: Research and Conservation, 2019)
Mahonia imbricata was reported for the first time from Manipur, India. This paper describes taxonomy, morphology, phenology, habitat requirements, ecology and world distribution of the species. On the basis of the examined specimens, notes and photographs for easy identification are presented.